Biologia de Meloidogyne exigua: II. Desenvolvimento pós-embriogênico em cafeeiro ’mundo novo’ - D’Arc de Lima, Rosângela; Ferraz, Silamar (Revista Ceres, 2025)
The development of Meloidogyne erigua after penetration in coffee roots was studied.